Scroogenomics : why you shouldn't buy presents for the holidays - Waldfogel, Joel, 1962- (Princeton University Press, 2009)
Economist Joel Waldfogel illustrates how our consumer spending generates vast amounts of economic waste--to the shocking tune of $85 billion each winter. He provides solid explanations to show us why it's time to stop the madness and think twice before buying gifts for the holidays. Gift giving is different than shopping for our own needs: we make less-informed choices, max out on credit to buy gifts worth less than the money spent, and leave recipients less than satisfied, creating what Waldfogel calls "deadweight loss." And this waste isn't confined to Americans--most major economies share in this orgy of wealth destruction. While recognizing the difficulties of altering current trends, he offers viable alternatives. By reprioritizing our gift-giving habits, Scroogenomics proves that we can still maintain the economy without gouging our wallets, and reclaim the true spirit of the holiday season.--From publisher description